2021
DOI: 10.1093/tas/txab002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bacillus subtilis PB6 on feedlot phase growth performance, efficiency of dietary net energy utilization, and fecal and subiliac lymph node Salmonella prevalence in spring placement yearling beef steers fed in southeastern South Dakota1,2,3

Abstract: Yearling crossbred beef steers [N = 238; initial shrunk body weight (BW) = 402 ± 31.2 kg] were used to investigate the influence of a Bacillus subtilis probiotic on animal growth performance, efficiency of dietary net energy (NE) utilization, carcass characteristics, and fecal and subiliac lymph node Salmonella prevalence during a 140-d finishing period at the Southeast Research Farm in Beresford, SD. Steers were allotted to 1 of 24 pens (N = 9–10 steers/pen) and assigned to 1 of 2 dietary treatments (12 pens/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
3
4
0
Order By: Relevance
“…Carcass characteristics, including HCW, dressing percentage, 12th-rib fat, longissimus muscle area, marbling score, USDA quality grade, and yield grade did not differ by treatment ( P ≥ 0.36). These results are consistent with other studies with B. subtilis PB6 supplementation to feedlot cattle ( Smock et al., 2019 ; Smith et al., 2021 ; Word et al., 2022 ). Likewise, Krehbiel et al.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Carcass characteristics, including HCW, dressing percentage, 12th-rib fat, longissimus muscle area, marbling score, USDA quality grade, and yield grade did not differ by treatment ( P ≥ 0.36). These results are consistent with other studies with B. subtilis PB6 supplementation to feedlot cattle ( Smock et al., 2019 ; Smith et al., 2021 ; Word et al., 2022 ). Likewise, Krehbiel et al.…”
Section: Resultssupporting
confidence: 93%
“…(2019) did not observe an effect of B. subtilis PB6 supplementation on finishing performance. Similarly, feedlot performance was not affected by B. subtilis PB6 supplementation to yearling steers ( Smith et al., 2021 ). Yet, supplementing B. subtilis PB6 to feedlot steers in a commercial feedyard tended to improve live cattle performance on deads and removals included basis ( Word et al., 2022 ).…”
Section: Resultsmentioning
confidence: 98%
“…However, it is important to note that the Salmonella prevalence in the Church and Dwight research database is biased due to repetitive sampling at Salmonella -challenged sites. The little Salmonella observed in the present study is consistent with other data in the Northern Plains ( Smith et al, 2021 ). The only time Salmonella was detected by Smith et al (2021) was when there was a heat event observed during fecal sampling.…”
Section: Resultssupporting
confidence: 93%
“…As Salmonella , E. coli , and C. perfringens are common pathogens found in cattle feces and are capable of causing foodborne illness ( Flach et al, 2022 ), it is essential to find alternative preharvest interventions to reduce these pathogen loads and help improve food safety. Bacillus subtilis -based direct-fed microbial ( DFM ) feed additives have been shown to reduce harmful pathogenic bacteria in the gastrointestinal tract ( Smock et al, 2020 ; Smith et al, 2021 ). Yeast cell wall ( YCW ) components of Saccharomyces cerevisiae have been shown to reduce inflammation and modulate immune function while also helping reduce pathogen loads ( Baines and Erb, 2013 ; Stefenoni et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported relatively low prevalence of Salmonella isolated from lymph nodes in cattle (Arthur et al, 2008; Bailey et al, 2017; Smith et al, 2021; Webb et al, 2017). Results from the current study support these findings as the average Salmonella prevalence isolated from lymph nodes was 8.4% (0.0–14.0%).…”
Section: Discussionmentioning
confidence: 99%